ENSURING THE QUALITY OF EDUCATION DURING MARTIAL LAW: THE ROLE OF DIGITAL TECHNOLOGIES - Свисюк, Олена; Білошицька, Зоя; Давидович, Степан (SWorldJournal, 2025)
The paper highlights the importance and role of digital technologies in ensuring the quality of education in the context of martial law in Ukraine. It considers the challenges associated with the destruction of infrastructure, population displacement, li